2001
DOI: 10.1046/j.1528-1157.2001.15100.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug Withdrawal in Patients with Temporal Lobe Epilepsy Undergoing Presurgical Video‐EEG Monitoring

Abstract: Summary:Purpose: To investigate antiepileptic drug (AED) withdrawal during video-EEG monitoring in adult patients with temporal lobe epilepsy (TLE).Methods: Between 1995 and 1997, 102 consecutive patients with refractory TLE were admitted to the epilepsy monitoring unit for presurgical evaluation. Patients were monitored with ongoing AEDs being rapidly decreased and discontinued in 4-6 days. The monitoring was continued until sufficient numbers of seizures were recorded. Serum AED levels were checked at admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…We used the clinical 4-hour period definition for seizure clustering. The rate of seizure clusters in the present study was similar to that reported in subjects who underwent presurgical evaluations 9,23. The duration of the first seizure in a cluster of seizures (median, 98s; range, 14–246s) was significantly longer than that of non-cluster seizures (median, 89s; range 4–1016s).…”
Section: Discussionsupporting
confidence: 87%
“…We used the clinical 4-hour period definition for seizure clustering. The rate of seizure clusters in the present study was similar to that reported in subjects who underwent presurgical evaluations 9,23. The duration of the first seizure in a cluster of seizures (median, 98s; range, 14–246s) was significantly longer than that of non-cluster seizures (median, 89s; range 4–1016s).…”
Section: Discussionsupporting
confidence: 87%
“…However, for adult patients with infrequent seizures who were taking multiple antiepileptic drugs (AEDs), a lengthy stay may be required for vEEG monitoring because of the unpredictability of their seizure occurrences. 4…”
Section: Prolonged Video-eegmentioning
confidence: 99%
“…Previous reports applying AED withdrawal showed 81.0-92.6% diagnostic yield, with one or more seizures confirmed in the monitored adult patients with infrequent seizures. 4,[6][7][8][9][10][11] There were various patterns of AED withdrawal in each institution. Therefore, the vEEG monitoring periods ranged from 1 to 37 days.…”
Section: Withdrawal Of Multiple Aedsmentioning
confidence: 99%
See 2 more Smart Citations